Highly sensitive aptasensor for oxytetracycline based on upconversion and magnetic nanoparticles. Issue 6 (16th February 2015) - Fang, Congcong; Wu, Shijia; Duan, Nuo; Dai, Shaoliang; Wang, Zhouping
Abstract : Schematic illustration of the highly sensitive aptasensor for oxytetracycline based on upconversion and magnetic nanoparticles. Abstract : A novel sensitive aptasensor was developed for the quantification of oxytetracycline (OTC) in this study. Artificial aptamer-modified magnetic nanoparticles (aptamer-MNPs) were employed as capture probes, and complementary oligonucleotide-modified upconversion nanoparticles (cDNA-UCNPs) were used as signal probes. Then, the probes were hybridized to form poly-network structure MNPs-UCNPs signal probes. Finally, when the target was introduced, the aptamer combined with the priority target and the signal probe was replaced. The proposed method achieved a linear range between 0.05 and 100 ng mL −1, and the limit of detection (LOD) was as low as 0.036 ng mL −1, benefiting largely from labeling with UCNPs, aptamer affinity and magnetic separation. Then, we successfully applied the method to measure OTC in milk samples and validated it by a commercially available enzyme-linked immunosorbent assay (ELISA) method. The results demonstrated that the method possessed high sensitivity and good selectivity for the determination of OTC and is applicable to the determination of OTC in food samples.